The use of peat as casing material in mushroom cultivation - Pardo-Giménez, A.; Zied, D. C. [UNESP]; Pardo-González, J. E. (My University, 2012)
The initiation and development of the carpophores of Agaricusbisporus (Lange) Imbach depend not only on the geneticcapacity of the mycelium to fructify but also on physical, environmental, chemical, nutritional and microbiologicalfactors. In fact, compost which is completely colonised by mycelium will not onits own produce mushrooms. It is therefore necessary to modifythe compost to initiate fructification. The casing layer is the materialused as a top covering of the compost and it is here that theecological modification that involves the change from the vegetativeto the reproductive growth phase takes place, and wherefructification occurs. Peat is the material most widely used as casing for mushroom cultivation throughout the world. Itswater- holding capacity and structural properties are widely acceptedas ideal for the purposes of casing. This chapter presents a review of casing and aspects of fruiting in relation with mushroom cultivation. The results of experimentation with different peat-based casing materials are discussed. ©2012 Nova Science Publishers, Inc.